Glass Furnace Controlling from Saving Energy Aspect - Klimenda, Frantisek; Skocilasova, Blanka; Skuthan, Petr; Močilan, Martin (Manufacturing Technology Journal, 2015)
The article is the possibility of energy saving of glass furnaces Bonacci when operating. A proposal to energy saving is aimed at changing of the control process of furnaces and installation of closing doors inlet and outlet ports of furnaces. By inlet and outlet ports of these continuous furnaces considerably leaks thermal energy when are not used (i.e. breaks at work). The doors are designed as a hollow panel, which is filled by isolation. This leads to a considerable saving of energy and to reduce of operating costs. The current control process of furnaces is now obsolete and can not flexibly changed it according a change of manufacturing products. The newly designed controlling systems is controls not only the kinematics, i.e. moving actuator of glass, but also temperatures in furnaces and newly inlet and outlet doors for closing of holes.
Keywords: Glass furnace; heat loss; construction of gates